Exploring the Scope of Integration of Integration of Indigineous knowledge of Tribal Communities of Jharkhand in Science Curriculum at Elementary Stage - Tigga, Anjali Catherine; Krishnan, Dhanya (SCHOOL SCIENCE, 2025)
It is widely known that local communities possess rich repositories of knowledge which are built upon their beliefs, practices and ways of living. National Education Policy 2020 suggests for school curricula which are deeply rooted in Indian contexts. In addition, sustainable ways of life offered by indigenous communities also justify the need for collecting and organising knowledge rooted in the profundity of indigenous societies. Considering science as a way of exploration of nature, it is imperative to appreciate vast knowledge of indigenous societies about nature. Attempt also has to be made to preserve and transmit them through school curricula and textbooks. In this context, this paper seeks to identify indigenous knowledge of tribal communities of Jharkhand by interviewing knowledge experts which would be deliberated for integrating into science curriculum at elementary stage. The study was also aimed at exploring the extent of integration of indigenous knowledge into the science curriculum and teachers’ perception regarding the integration by conducting interviews with the teachers, Focus Group Discussion with students and science classroom observations. The study paved ways for collecting indigenous knowledge of tribal communities that can be related to the concepts of science in the existing curriculum at elementary stage. It is also found that the teachers have positive perception towards the idea of integrating indigenous knowledge as it is intended to make the science learning more contextual. However, limited integration could be found in the elementary science classes of Jharkhand. The scope for integration of indigenous knowledge of tribal communities at elementary stage science curriculum is found to be plenty. Positive perception of students regarding integration of indigenous knowledge in science curriculum is promising. This demands efforts from curriculum planners and textbook developers to integrate indigenous knowledge into science curriculum to strengthen the bridge between the realms of science and indigenous knowledge.